New species of Dugdaleiella, gen. nov., Kozloviella, gen. nov., and Pfitzneriella Viette from upper elevation Andes of Ecuador and Peru (Lepidoptera: Hepialidae) - Grehan, John R.; Mielke, Carlos. G. C. (Zootaxa, 2018)
Six new Hepialidae species are described from high elevation habitats in the Andes of Peru and Ecuador. One species is assigned to the genus Kozloviella gen. n., K. viazmenskyi sp. n., from Peru, and five to the genus Pfitzneriella Viette, 1951: P. antonkozlovi sp. n., P. olafi sp. n., P. titarenkoi, sp. n., P. yuliyakovalevae sp. n. from Peru and P. rawlinsi sp. n., from Ecuador. Dugdaleiella gen. n., is proposed to accommodate the Ecuadorian species Dugdaleiella monticola (Maassen, 1890) comb. n., formerly placed in Pfitzneriella. The taxonomic (but not the phylogenetic) status of P. lucicola (Maassen, 1890) is unaltered pending future opportunity to examine the type series. Preliminary phylogenetic analysis of the morphological characters supports Kozloviella gen. n., and Pfitzneriella as sister taxa, and separates P. titarenkoi sp. n., from the other species of Pfitzneriella. We suggest that the ancestor of these high elevation genera already occupied a pre-Andean upland habitat across Peru and Ecuador and this ancestor further diverged into the modern genera and species during the Andean orogeny. We consider it likely that there is a considerable diversity of endemic high elevation Hepialidae that remains to be discovered in the eastern Andes between Venezuela and Bolivia.